If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 8x + 5 = 4x + 13 Reorder the terms: 5 + 8x = 4x + 13 Reorder the terms: 5 + 8x = 13 + 4x Solving 5 + 8x = 13 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + 8x + -4x = 13 + 4x + -4x Combine like terms: 8x + -4x = 4x 5 + 4x = 13 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + 4x = 13 + 0 5 + 4x = 13 Add '-5' to each side of the equation. 5 + -5 + 4x = 13 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = 13 + -5 4x = 13 + -5 Combine like terms: 13 + -5 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2

| 13b-1=4b-19 | | 2(x-4)+3=2x-5 | | 149-4x=6x+19 | | 3x+1=11-2x | | 3X-(2X+10)-5=9X+2(x+7.5) | | 7(2a-1)=21 | | 6x+6=-111-7x | | -5u=-1 | | 3(2x+1)= | | 2(2x-3)= | | -150-8x=9x+20 | | 6(x-4)= | | 8(2x-3)= | | -3(x+4)= | | -2(3x-1)= | | -10(2x+0.2)= | | -4=-15-3x | | y=-5x | | 9-9x=109-44x | | 6z-8=-44 | | Y-5=-4 | | 0.2(x-6)=1.0 | | 27-(x+9)=5x-6 | | 45-9x=75 | | 3x-4y=20 | | 220-3x=33x+20 | | x+29-3=2x+44 | | y+3=0 | | 7+2(5x-3)= | | 7+x=.5(4x-2) | | 9a=7a-8 | | 2x+10=17-3x | | 9a=7a-(8) | | 5*w=10 | | -4*s=36 | | 4Y-12=44 | | 2m-7=3(m+8) | | 4Y-12=44X | | -3a=12 | | 1.3x=-2 | | 8x+10=4x+30 | | 3(2x+7)-5=22 | | 15+5x=27+3x | | 6x-12=4x-4 | | 3(5x-2)=4(3x+6) | | 10+3x=x+16 | | 7(x+4)=10(x+1) | | 97=(-5x)-3x+1 | | 3(2x-3)=3x+15 | | 4(x+2)=2(x-2) | | 97=-5x-3x+1 | | 5(x+3)=2(x-3) | | 5(2x+3)=2(2x+3) | | 5+y=21 | | 8(x+5)=3x+8 | | 5(2x-3)=3(3x+2) | | 16=4x | | 2a=10 | | 2(a+3)= | | 4(2-x)=5(x-2) | | 4n=12 | | 3y=15 | | (x-5)(x-2)=0 | | x(x+3)=1 | | 5(x-4)=2(x-7) |